Relationship between Art and Design Students’ Technical and Managerial Skill Traits and Their Entrepreneurial Skill Traits - Odewole, Peter Oluwagbenga; Adeloye, Adebayo Abiodun; Afolabi, Benjamin E. Fisayo; Oladesu, Johnson Olarinde; Oyinloye, Michael Abiodun; Uzzi, Festus Osarumwense (Journal of Technical Education and Training, 2024)
The unavailability of jobs for graduates has become a gross concern in developing countries such as Nigeria, which is not necessarily contingent on graduates from any specific course of study, including art and design education. It is thus evident that proficiency in artistic or creative talent alone is insufficient to guarantee a thriving art and design career and the need to develop the required entrepreneurial propensity. This study, therefore, aims to evaluate the entrepreneurial skills and traits of art and design students in Nigerian higher education institutions (HEIs) as a remedy for stimulating their entrepreneurial tendencies. The hypothesized model of art and design students’ entrepreneurial traits was developed based on the theoretical framework developed from the literature as a three-factor construct (Model 1.0) comprising technical/soft skills, managerial skills, and entrepreneurial skills. Data was obtained using a structured Likert scale questionnaire of 36 items adapted from Yilzman & Sunbul’s entrepreneurial scale from a sample of 186 art and design students. Data was analysed using descriptive statistics and the Covariance-based Structural Equation Modelling (CB-SEM) via the IBM SPSS Statistics 26 and IBM SPSS Amos 26 Graphics software. The model fit results reveal that the goodness-of-fit statistics indexes fell within the acceptable range. The results of the hypotheses testing of the model show that no significant association exists between art and design students’ technical and entrepreneurial skill traits. However, there is a significant association between their managerial and entrepreneurial skill traits. The outcome of this research has implications for TVET institutions in the arts and design field further to promote the development of students’ inherent entrepreneurial traits to boost their entrepreneurial tendencies.